Hidden and Sacred : African American Cemeteries in Eastern North Carolina - Smith, Jonathan (East Carolina University, 2010)
The purpose of thesis is to identify an Eastern North Carolina African American Burial Pattern through the survey of Black Bottom Cemetery and the comparison of this cemetery to others in Eastern North Carolina as well as the Southeastern United States. Black Bottom Memorial Cemetery is a community cemetery comprised of over 600 marked and unmarked graves in which the earliest marked burial dates to 1907 and the most recent burials to 1999. Grave markers used range from locally crafted folk styles from materials such as concrete to commercial marble monuments. The cemetery began on the highest ground within the plot and expanded to nearby low-lying areas. During the Civil Rights era of the 1950s and 1960s a change occurred in the cemetery in which family plots moved to a more visible location closer to the road bordering the property, the style of markers changed to a flat slab provided by the funeral home, and rows of individual burials, as opposed to groups of family plots, were established in the eastern section of the cemetery.     In Black Bottom Memorial Cemetery grave decorations are found in scatters centering on individual graves or grave groups and appear to have broken over time due to natural factors. The vessels are predominately decorated household items such as painted ceramics and molded glass. Grave orientation and grouping is another key characteristic of African American cemeteries. Graves in the Black Bottom Memorial Cemetery are primarily arranged in family clusters, orientation varies widely and seems to be of secondary importance to proximity to family clusters, in other words, burial near family was of greater importance than maintaining a strict east-west alignment.   Comparison with other, roughly contemporary, African American cemeteries in the Southeast reveals similar characteristics in grave decorations and grave alignment. Data from the survey of Black Bottom Memorial Cemetery and the comparison cemeteries suggests that large amounts of ceramic and glass fragments or vessels, folk or locally made markers, and graves clustered in family groups rather than in ordered plots are strong indicators of post-emancipation through the Civil Rights era African American cemeteries. After the Civil Rights Movement, grave decoration shifted to alternative decorative materials such as banners, solar lights, and other items. The higher visibility of the graves suggests that a change in attitudes regarding entitlement to a place in mainstream culture occurred but that traditional practices of grave decoration continue in a modified form.
Keywords: Archaeology; African American studies; Folklore; African American cemeteries--North Carolina--Beaufort County; Cemeteries--North Carolina--Beaufort County; Black Bottom Memorial Cemetery (Belhaven, N.C.); Burial--North Carolina--Beaufort County; Cemeteries--Recording--North Carolina--Beaufort County